Enhancing Educational Quality through School Committees: Teachers' Perceptions of Curriculum Implementation - Aliyyah, Rusi Rusmiati; Nisa, Shofia Hanna (Nurul Jadid University, Probolinggo, East Java, Indonesia, 2025)
This study aims to analyze elementary school teachers' perceptions of the role of school committees in curriculum implementation as an effort to improve educational quality. The background to this research stems from the challenges of uneven distribution of educational quality in Indonesia, despite the implementation of various policies. This study employed a qualitative approach with thematic analysis based on the Braun & Clarke model. Thirty-five teachers participated in the study, with data collected through semi-structured interviews and analyzed using NVivo 12 software. The findings suggest that school committees play a crucial role in channeling parental aspirations, enhancing transparency and accountability in budget management, and fostering effective communication between schools and the community. However, obstacles exist, such as differing visions, weak coordination, low public literacy regarding the committee's role, and a non-participatory formation process. Nevertheless, the committees have proven to support the implementation of school programs and expand educational social networks. This study's original contribution lies in emphasizing teacher voice as a key indicator in assessing the effectiveness of participatory governance. These findings offer strategic implications for enhancing collaboration among schools, parents, and the community in improving the quality of elementary education.